Comparative study of ketorolac versus butorphanol as an adjuvant in Intravenous regional anaesthesia (IVRA) - Kataria, Amar Parkash; Pal Attri, Joginder; Singh, Nirvair; Thakur, Millind (International Journal of Medical Research and Review, 2016)
Background: Intravenous regional anaesthesia (IVRA) is simple, effective technique for upper limb orthopaedic surgeries specifically in developing countries like India because of cost- effectiveness. IVRA is also called Bier’s block after the name of its inventor August Bier. Aim: Present study was carried out to evaluate the effects of adding either butorphanol or ketorolac to lignocaine during Bier’s block. Materials and Methods: In a prospective randomized double blind study, 60 patients of age group 18-65 years of either sex with weight range of 65-70 kg of ASA grade I- III were randomly allocated into two groups of 30 each. Group I received butorphanol 1mg added to 3mg/kg lignocaine and group II received ketorolac 30 mg added to 3mg/kg lignocaine. Sensory and motor block onset, regression time, intraoperative and postoperative VAS score, duration of analgesia, total analgesic consumption in first 24 hr and side effects were noted. Statistical analysis of data was based on chi square test and post hoc test. Results: Demographic profile in both the groups was same. Duration of analgesia was significantly prolonged in group II(10.8 ±6.42) as compared to group I(3.02±1.52). In both the groups, patients remained haemodynamically stable and side effects and complications were also comparable. Conclusion: Ketorolac with lignocaine in IVRA provides prolonged post-operative analgesia as compared to butorphanol and lesser number of patients require rescue analgesia intraoperatively as well as postoperatively without any significant side effects.